Public spending, income inequality and economic growth in Asian countries: A panel GMM approach - Yobouet Thierry Bienvenu Gnangoin; Liangsheng Du; GuyRoland Assamoi; Akadje JeanRoland Edjoukou; Diby François Kassi (Economies, 2019)
This paper offers an empirical examination of the relationship between government spending's, income inequality, and economic growth by using the case of 19 Asian countries from 2002 to 2017. For this purpose, the paper uses robust difference-GMM estimation and panel granger causality test. We found that gross domestic investment and regulatory quality are the main variables that contribute to these countries' economic growth. While current government consumption reduces economic growth. Also, government expenditure on education and regulatory quality granger cause economic growth in these countries. However, the effect of government expenditure on education on economic growth is not significant. So, to increase their economic growth, this study recommends these countries' governments to encourage gross domestic investment, maintain regulatory quality and reduce their current consumption. This study also concludes that income inequality has no impact on these countries' economic growth for this period.
Keywords: C23; C26; H52; O53; 330; Asian countries; economic growth; income inequality; panel data; public spending